2023
DOI: 10.3390/biom13050805
|View full text |Cite
|
Sign up to set email alerts
|

mef2ca and mef2cb Double Mutant Zebrafish Show Altered Craniofacial Phenotype and Motor Behaviour

Abstract: The transcription factor MEF2C is crucial in neuronal, cardiac, bone and cartilage molecular processes, as well as for craniofacial development. MEF2C was associated with the human disease MRD20, whose patients show abnormal neuronal and craniofacial development. Zebrafish mef2ca;mef2cb double mutants were analysed for abnormalities in craniofacial and behaviour development through phenotypic analysis. Quantitative PCR was performed to investigate the expression levels of neuronal marker genes in mutant larvae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Single-cell and spatial omics techniques provide excellent tools to study musculoskeletal disorders at the cellular level. 53 Adrião et al 54 conducted an analysis of mef2ca; mef2cb double mutant zebrafish, D. rerio for abnormalities in craniofacial and behaviour development through phenotypic analysis and found transcription factor myocyte enhancer factor 2 is crucial in neuronal, cardiac, bone and cartilage molecular processes and craniofacial development. They performed quantitative PCR to investigate the expression levels of neuronal marker genes in mutant larvae and analysed motor behaviour by checking the swimming activity of 6 dpf larvae and revealed that mef2ca; mef2cb double mutants display several abnormal phenotypes during early development, such as severe craniofacial phenotype, developmental arrest due to the disruption of cardiac oedema and evident alterations in behaviour.…”
Section: The Mechanism Regulating Deformitiesmentioning
confidence: 99%
“…Single-cell and spatial omics techniques provide excellent tools to study musculoskeletal disorders at the cellular level. 53 Adrião et al 54 conducted an analysis of mef2ca; mef2cb double mutant zebrafish, D. rerio for abnormalities in craniofacial and behaviour development through phenotypic analysis and found transcription factor myocyte enhancer factor 2 is crucial in neuronal, cardiac, bone and cartilage molecular processes and craniofacial development. They performed quantitative PCR to investigate the expression levels of neuronal marker genes in mutant larvae and analysed motor behaviour by checking the swimming activity of 6 dpf larvae and revealed that mef2ca; mef2cb double mutants display several abnormal phenotypes during early development, such as severe craniofacial phenotype, developmental arrest due to the disruption of cardiac oedema and evident alterations in behaviour.…”
Section: The Mechanism Regulating Deformitiesmentioning
confidence: 99%